The Solar atmosphere. [Motion picture] - Zirin, Harold; California Institute of Technology (Harold Zirin. Released by California Institute of Technology, 1972)
Discusses various aspects of the solar atmosphere, including granulation, development of sunspots, spicules, flares and flare waves, surges, and prominences.
Keywords: Solar atmosphere